FLOUTING MAXIM ON ENGLISH RADIO PROGRAM IN YOGYAKARTA - Agustinus Hary Setyawan (Universitas PGRI Yogyakarta, 2021)
As an event that is on the rise lately, English radio talk show in Yogyakarta provides various interesting topics with various invited guest from different background which create rich conversations among the radio announcer and the guest. When the interlocutor commits a flouting maxim, the radio broadcasting context plays an important role in interpreting the meaning of the speech. Hence, the purpose of this study is to determine the types of flouting maxim and the reason why it is flouted. This research was designed as descriptive qualitative research methods. Sources of data in this study were conversations between radio announcers and guests who have the flouting maxim utterance in English radio broadcasting program. The finding shows 10 flouting maxim data in English radio talk shows in Yogyakarta. There were 40% flouting of the maxim of quantity, 30% of the flouting of the maxim of quality, 20% of the flouting of the maxim of relevance and 10% of the flouting of the maxims of implementation. The announcer and guest in the English radio broadcasting in Yogyakarta floutÂ theÂ maximsÂ deliberately due to several factors such as providing detailed information, convincing, making humble attitude, saving face and creating a relaxed situation with a joke or indirect message.